Traction Trebuchet - Siri Hjelsvold; Simon McCallum (EXARC Journal)
The trebuchet, in all its forms, was very much in vogue in the reenactment and research community in the 1980s and 1990s. Several museums around the world have also built their own, with Middelaldercenteret in Nykøbing Falster in Denmark as one of the first modern examples of counterweight trebuchet (Hansen, 1989). Despite the multitude of builds, very little has been published about the process. When it comes to the traction machines, the authors are only aware of Tarver’s influential article (1995). From the historical perspective, Paul Chevedden (1998; 2000), amongst others, brought focus to the traction-based version of the machine, which is more commonly considered as an introductory note of the more awe-inspiring counterweight. At the Tower of London, a traction trebuchet clearly modelled on counterweight machines uses a pulling crew of about 4 people, throwing across the grass along the length of the outer walls (This seems to be their standard number, based on a range of YouTube videos taken by members of the public). This is the beginning of our work to change this state of the evidence of traction trebuchets, and attempt to see what the results of our experiments can do to help understand the physical realities of traction trebuchets at war. While those who specialize in traction trebuchets often have some tactical knowledge of its attributes, many historians of siege warfare more generally rely heavily on historical assumptions that do not necessarily stand up to critical evaluation. “While somewhat simpler to construct than its ancient predecessor, the logistical requirements of the traction trebuchet were just as great or even greater, and it needed even more trained crews and engineers to operate effectively, as well as a large number of expert craftsmen.” is only the most recent statement by Petersen (2013, p.409) of commonly accepted attributes. This is primarily accurate for traction trebuchet based on counterweight designs, principles and purposes. In this paper, we aim to illustrate why this is, in our experience, an inaccurate view of the smaller scale machines.